Internationalization field lab of PS: an in-depth analysis of the United States - Casaca, Carolina Dos Santos Da Rocha (2022)
Internationalization is a strategic challenge for small companies. This paper aims to provide an analytic procedure for the Portuguese luxury real estate agency of PS by defining the target market for expansion, an appropriate market entry mode, and an applicable marketing plan along with a financial forecast. Firstly, literature concerning the international market selection for small and medium enterprises was analyzed. Secondly, an in-depth analysis of the US was conducted and, although it has inequalities, different state laws, and intense competition, the US reveals to be highly attractive mainly due to its large customer base and a high sales potential.